Outcome of Different Surgical Interventions in Management of Emphysematous Pyelonephritis: A Retrospective Cohort Study from Dharwad, India - Revanasiddappa Kanagali; Muralidhar Achar; Pramod Makannavar; Srinivas Kalabhavi (Journal of Clinical and Diagnostic Research)
Introduction: Emphysematous Pyelonephritis (EPN) is a rare, life-threatening infection of the renal parenchyma characterised by gas formation within the kidney and surrounding tissues. When not promptly diagnosed and treated, this condition presents with a mortality rate ranging from 20% to 80%. Aim: This study aimed to evaluate the outcomes of different surgical interventions in managing EPN, focusing on minimally invasive interventions {Double J Stent (DJS), Percutaneous Nephrostomy (PCN), Percutaneous Drainage (PCD)} and nephrectomy. Materials and Methods: A retrospective cohort study was conducted at SDM College of Medical Sciences and Hospital, Dharwad, Karnataka, India, examining 80 cases of EPN over a 54-month period from January 2017 to June 2023. Data were collected from hospital records, including clinical notes, laboratory results, imaging studies, and surgical reports. The study assessed demographics, clinical presentation, laboratory investigations, imaging studies, treatment details, and patient outcomes. Descriptive statistics were used for demographic and clinical characteristics and Chi-square test was applied for categorical variables. A p-value of <0.05 was considered statistically significant. Results: The study included 80 patients with a gender distribution of 48.8% female and 51.2% male, with a mean age of 57.9±12.2 years. Flank pain (91.3%), fever (86.3%), and dysuria (36.3%) were the predominant clinical manifestations. Laboratory evaluation revealed significant findings, including anaemia (52.5%), renal dysfunction (56.3%), and sepsis (61.3%). Escherichia coli were the primary causative organism, identified in 34 patients (42.5%). Class 2 EPN was the most prevalent classification, occurring in 25 patients (31.3%). Hypotension (p-value=0.015), elevated Glycated haemoglobi (HbA1c) levels (p-value=0.018), and the need for dialysis (p-value=0.008) were significantly associated with mortality. Minimally invasive interventions were predominantly successful, with various drainage procedures employed: unilateral DJS (48.8%), bilateral DJS (27.5%), PCN (3.8%), and PCD (18.8%). Nephrectomy was required in only 5% of cases. Conclusion: This study supports the efficacy of minimally invasive intervention approaches for EPN, thereby reducing the necessity for nephrectomy. Prognostic indicators, including hypotension, elevated HbA1c, and the requirement for dialysis, warrant careful monitoring. Minimally invasive interventions, coupled with targeted antibiotic therapy, are validated as a preferred treatment for EPN.